Risk assessment framework and criteria for major accidental release to the environment in Malaysia - Ali, Mohamad Wijayanuddin (2002)
Events which could be considered a "major accident to the environment" are very diverse in nature. The UK Department of the Environment (DoE) has published a "Green Book" giving the definitions of such events. UK AEA Technology has attempted to define tolerability criteria for accidents to the environment in terms of an environmental severity index (ESI) which is the ratio of the severity of the accident to that of the most appropriate reference accident from the DoE Green Book. These criteria were proposed only for releases to rivers. This paper describes the development of risk assessment framework based on an environmental risk index (ERI) proposed (in tradition of the ICI Mond Index method for flammable hazards). The ERI is a measure of the total severity and probability of a wide range of possible environmental consequences which could result from any particular release. The tolerability criteria developed for the ESI method can also be used with the ERI. The ERI method is designed to facilitate rapid screening of the environmental risks from a variety of release scenarios. The effects of various methods for prevention and mitigation of the release can be taken into account. The framework will be described with reference to a hypothetical case study involving an accidental release of a pesticide into the River Don in Sheffield from a manufacturing plant. This has led to a number of improvements to the method, including a revision of the tolerability criteria proposed by AEA Technology. As for Malaysia, a similar approach could be proposed and adopted, as necessary.